Towards Building Capacity in Climate Information Systems and Climate Smart Agriculture in Africa - Daouda, Kone; Nakayiwa, Florence; Majaliwa, Jackson Gilbert Mwanjalolo; Ekepu, David (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate change is one of the major concerns mankind will have to deal with for a long period of time. Judicious use of adaptation and mitigation measures are the only avenues for addressing climate change and associated impacts. Building climate science literacy is vital for citizens to understand the impacts of climate change and develop solutions to mitigate climate change and adapt to its effects. AICCRA-RUFORUM partnership aimed at developing continental-wide top-priority course modules in order to build capacity at different levels on the continent. This document briefly explains the process through which the continental-wide climate change top-priority course modules were developed and implemented. Out of the 11 modules identified by RUFORUM and WASCAL, seven have been drafted and 6 are currently readily available for training. These include an introduction to CSA and CIS, the Policy framework of CSA and CIS, Climate-smart crop-livestock-aquaculture integration, climate-smart nutrient, and water management in crop production soil-carbon sequestration, and crop production. Clean energy options for sustaining agricultural productivity, abiotic and biotic management in crops, and disaster risk management in crop production are being finalized.